2015
DOI: 10.1080/13506285.2015.1055852
|View full text |Cite
|
Sign up to set email alerts
|

Seeing is knowing? Visual word recognition in non-dyslexic and dyslexic readers: An ERP study

Abstract: The aim of the current study was to investigate whether phonological/semantic processing of the word takes place simultaneously with, or following, the early processing of its visual features. Event related potentials (ERPs) were recorded in thirteen dyslexic (4 female) and fourteen non-dyslexic (6 female) native English speaking young adults in two lexical decision tasks. In Task 1 participants had to make an orthographic lexical decision to distinguish frequently used words (W) from pseudohomophones (PH1) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
2
2
1
Order By: Relevance
“…A late P300 was identified in some individuals, however it was not present in all participants and, therefore, was excluded from further analysis. Each participant's ERP peak amplitudes were computed within the time windows established in the group average ERPs and automatically measured at the peak maximum (e.g., Taroyan, 2015). Peak amplitudes and latencies for all single channels were averaged into side-specific area groups (O, PO and P, for left and right hemisphere separately; see Figure 1) in order to optimize signal to noise ratio and increase statistical power (Oken and Chiappa, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…A late P300 was identified in some individuals, however it was not present in all participants and, therefore, was excluded from further analysis. Each participant's ERP peak amplitudes were computed within the time windows established in the group average ERPs and automatically measured at the peak maximum (e.g., Taroyan, 2015). Peak amplitudes and latencies for all single channels were averaged into side-specific area groups (O, PO and P, for left and right hemisphere separately; see Figure 1) in order to optimize signal to noise ratio and increase statistical power (Oken and Chiappa, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, though, no evidence was found that suggests differences in lexicality, orthographic or phonological, influence P1-O amplitude. Therefore, in contrast to some previous findings (e.g., Segalowitz & Zheng, 2009;Taroyan, 2015), P1-O amplitude does not appear to reflect either orthographic or phonological lexicality when stimulus conditions are closely controlled.…”
Section: Behavioural Performancecontrasting
confidence: 99%
“…This follows several reports from Hauk and colleagues (e.g., Hauk, Davis, et al, 2006;Hauk et al, 2012;Hauk, Patterson, et al, 2006) and others (e.g., Emmorey et al, 2017), supporting the notion that P1-O amplitude does not reflect lexicality or word recognition per se (Gibbons et al, 2022;D. Zhang et al, 2014), refuting claims of larger P1 amplitudes to real words (e.g., Segalowitz & Zheng, 2009) and to pseudowords (e.g., Taroyan, 2015). Not only did the results of the current study suggest that P1-O amplitude did not differ based on orthographic lexicality, but, importantly, did not meaningfully differ in any group.…”
Section: Behavioural Performancesupporting
confidence: 86%
See 1 more Smart Citation
“…Nevertheless, adult dyslexics seem to have a more diffuse, bilateral reduction of ERP responses. Schulte-Körne et al (2004b) did not find any differences in the P200 amplitude and latency in dyslexic children while another study (Taroyan, 2015) found longer latencies for dyslexics. In another study by Schulte-Körne, Bartling, Deimel, and Remschmidt (2004a) the researchers investigated in-motion-onset visual evoked potentials (i.e.…”
Section: Why Is This Component a Possible Biological Marker For Readimentioning
confidence: 89%